The Diversion of Abbay/ Nile by Ethiopian Emperors: Claims and Disclaims - Bayu, Yeshambel Kindie (Ethiopian Journal of Social Sciences, 2020)
After Egypt occupied by the Arabs in 641, the relationship between Christian Ethiopia and Muslim Egypt was quarrelsome. Successive Muslim leaders of Egypt continue to convert Christians forcefully and this kind of maltreatment against Copts worsens the relationship between the two countries. In retaliation, Ethiopian Emperors took different measures against Muslim leaders. Sometimes they have invaded Upper Egypt and at another time diverted the course of Abbay so as to compel Egyptian Sultans with their request. Accordingly, Egyptians had been encountered a terrible famine because of the diversion of Abbay, to mention some, from 963 to 969, 1066 to 1072 and, 1199 to 1202. Regrettably, however, the ability of Ethiopian Emperors to divert the course of Abbay in order to stop the persecution of Copts considered as a myth. This paper attempted to examine medieval sources of Egypt and Ethiopia and offers substantial evidence as Abbay was diverted by Ethiopian Emperors.